Transdermal Delivery of Ondansetron HCl from Thermoreversible Gel Containing Nanocomposite - Parhi, Rabinarayan; Reddy, Surya S.; Swain, Suryakanta (Current Nanomaterials, 2019)
Background: Application of thermoreversible gel can be a solution to the low residence time of the topical dosage forms such as normal gel, ointment and cream on the skin surface. Addition of another polymer and a nanocomposite can improve the poor mechanical strength and fast drug release of poloxamer 407 (POL 407) gel. Therefore, it is essential to add xanthan gum (XG) and graphene oxide (GO, thickness 1-2 nm, lateral dimension 1-5 μm) to POL 407 gel to enhance the mechanical strength and to sustain the drug release from the gel. Methods: Thermal gel of ondansetron hydrochloride (OSH) containing nanocomposite was prepared by adopting cold method. Interaction between drug and polymers was studied using FTIR method, morphological investigation was carried out by optical and scanning electron microscopy method, and rheological study was performed employing rotational rheometer equipped with a cone/plate shear apparatus, gelation temperature by glass bottle method and ex vivo permeation study was performed with cylindrical glass diffusion cell. Skin irritation potential was measured using rat as a model animal. Results: The FTIR spectrum of the selected gel showed that there is shifting of O-H stretching vibration of a hydroxyl group from 3408.72 to 3360.49 cm-1 and appearance of a new band at 1083.01 cm-1. The spectrum of the selected gel also showed the absence of characteristic peaks of GO at 1625.49 cm- 1. This result indicated that there may be an interaction between OSH and GO and hydrogen bonding between XG and POL 407. The gelation temperature was found to be decreased with the increase in GO content from 14.1±1.21°C 13±0.97°C. SEM micrograph demonstrated the uniform dispersion and intercalation of GO sheets in the gel. All the gel formulations showed a pseudo-plastic flow. Ex vivo permeation study (for 24 hr) exhibited highest (6991.425 μg) and lowest (2133.262 μg) amount of drug release, for OG1 and OG5, respectively. This is attributed to an increase in viscosity which led to a decrease in drug permeation across the abdominal skin of rats. The OG1 formulation (without GO) showed the highest flux of 76.66 μg/cm2/h, permeability coefficient (Kp) of 5.111× 10-3 cm/h and enhancement ratio of 3.277 compared to OG5 containing highest amount (9% w/w) of GO. The selected gel was found to be physically stable and there was minimum irritation score. Conclusion: All the above results indicated that thermal gel containing nanocomposite sustained the drug release and can be considered as an alternative to the orally administered tablet of OSH.
Keywords: Transdermal delivery